Pathologic Assessment of Rectal Carcinoma after Neoadjuvant Radio(chemo)therapy: Prognostic Implications. (5th October 2015) - Hav, Monirath; Libbrecht, Louis; Ferdinande, Liesbeth; Geboes, Karen; Pattyn, Piet; Cuvelier, Claude A.
Abstract : Neoadjuvant radio(chemo)therapy is increasingly used in rectal cancer and induces a number of morphologic changes that affect prognostication after curative surgery, thereby creating new challenges for surgical pathologists, particularly in evaluating morphologic changes and tumour response to preoperative treatment. Surgical pathologists play an important role in determining the many facets of rectal carcinoma patient care after neoadjuvant treatment. These range from proper handling of macroscopic specimens to accurate microscopic evaluation of pathological features associated with patients' prognosis. This review presents the well-established pathological prognostic indicators and discusses challenging features in order to provide both surgical pathologists and treating physicians with a checklist that is useful in a neoadjuvant setting.